The dose‐effect model is good enough. Issue 3 (4th August 2020) - Schuler, Keke; Kilmer, Elizabeth D.; Callahan, Jennifer; Dziurzynski, Kristan; Swift, Joshua
Abstract: Although there is wide agreement on the general efficacy of psychotherapy, two prominent models on the trajectories of change in psychotherapy over time, the dose‐effect (DE) model and the good‐enough level (GEL) model, indicate competing trajectories of change. According to the DE model, the course of treatment follows the shape of a negatively accelerating curve, even though each session of psychotherapy is conceptualised as providing an equivalent dose of treatment. In contrast, the GEL model suggests that there is a linear relationship between psychotherapy response and treatment length that is idiographic for each client, depending on the number of sessions attended. The aim of the current study was to compare these two models in a sample of 399 adult psychotherapy clients. Session‐by‐session outcome was tracked using the Outcome Questionnaire‐45.2 in tandem, and multilevel modelling was used for the analyses. Results indicate that the DE model fits the data better than the GEL model, although the difference in model fit was small. Support for the DE model over the GEL model was further evident in a subsample of prototypical clients—that is, those who did not experience problems with the therapeutic alliance, social support or stressful life events. Findings from the present study add to the existing literature comparing the DE and GEL models and have implications on outcome monitoring in psychotherapy services.